Über Geld und Geldtheorien - Chick, Victoria (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2001)
Different ways of studying monetary theory are discussed. Chick compares the roles and functions, money acquires in the neoclassical general equilibrium model, in Keynesian as well as in circular flow theories. She argues in favour of an economic theory, which is open to historical time and the evolution of institutions. Otherwise economic theory will be depleted of social relevance.